Failure of chemotherapy in the first reported cases of Acanthamoeba keratitis in Pakistan - Siddiqui, Ruqaiyyah (Maney Publishing, 2014)
Acanthamoeba keratitis is a painful and progressive infection of the cornea that can result in loss of vision. Here, for the first time in Pakistan, we report two cases of Acanthamoeba keratitis. The first patient was a 37-year-old female who presented with severe itching, redness, pain, along with loss of vision. The patient was a regular soft contact lens wearer. The second patient was a 25-year-old female who had been using soft contact lenses for the past two years. She presented with a burning sensation and extreme pain, along with loss of vision. Both patients were treated for a possible microbial keratitis with topical moxifloxacin hydrochloride drops, vancomycin drops, propamidine isethionate ointment, amphotericin B drops, and amikacin drops. However, the response was inadequate and both patients were referred for corneal transplant. Acanthamoeba castellanii was isolated by placing contact lenses and contact lens cases on non-nutrient agar plates containing a lawn of non-invasive Escherichia coli K-12 HB101 bacteria. The polymerase chain reaction (PCR) using genus-specific probes confirmed the identity of Acanthamoeba spp., whereas the morphological characteristics of trophozoites and cysts were suggestive of A. castellanii in both cases. With growing use of contact lenses for vision correction/cosmetic use coupled with sub-standard lens care in this region and the possibility of non-contact lens-associated Acanthamoeba keratitis, a need for increased awareness of this sight-threatening infection is discussed further.